The impact of basic dermatology education and training on primary healthcare providers in KwaZulu-Natal, South Africa - Pumeza U. Makaula; Antoinette V. Chateau; Richard J. Hift; Ncoza C. Dlova; Anisa Mosam (South African Family Practice)
Background: Dermatological diseases are amongst the commonest reasons for consultation at primary care level. Yet, dermatology teaching in medical and nursing curricula is inconsistent and often insufficient to enable medical and nursing professionals to manage these conditions effectively.